Ethiopia: Impacts of the Ukraine and Global Crisis on Food Systems and Poverty: Updated 2022-07-22 - Diao, Xinshen; Dorosh, Paul; Kedir Jemal, Mekamu; Taffesse, Alemayehu Seyoum; Thurlow, James (2022)
Presentation prepared by Xinshen Diao, Paul Dorosh, Mekamu Kedir Jemal, Alemayehu Seyoum Taffesse, and James Thurlow, all with the International Food Policy Research Institute, Washington, DC. This is part of the Global Crisis Country Series.